STRENGTHENING THE MATERIAL AND TECHNICAL BASE OF PHYSICAL EDUCATION AND SPORTS IN THE REPUBLIC OF UZBEKISTAN (1991-2019) (TAMADDUN NURI JURNALI, 2025)
The article analyzes the strengthening of the material and technical base of physical education and sports in the Republic of Uzbekistan in 1991-2019 and its main results using materials from scientific literature and primary sources.